Ion Transport in Eryptosis, the Suicidal Death of Erythrocytes - Föller, Michael; Lang, Florian (Frontiers in Cell and Developmental Biology, 2020)
Erythrocytes are among the most abundant cells in mammals and are perfectly adapted to their main functions, i.e. the transport of O2 to peripheral tissues and the contribution to CO2 transport to the lungs. In contrast to other cells, they are fully devoid of organelles. Similar to apoptosis of nucleated cells erythrocytes may enter suicidal death, eryptosis, which is characterized by the presentation of membrane phosphatidylserine on the cell surface and cell shrinkage, hallmarks that are also typical of apoptosis. Eryptosis may be triggered by an increase in the cytosolic Ca2+ concentration, which may be due to Ca2+ influx via non-selective cation channels of the TRPC family. Eryptosis is further induced by ceramide, which sensitizes erythrocytes to the eryptotic effect of Ca2+. Signaling regulating eryptosis further involves a variety of kinases including AMPK, PAK2, cGKI, JAK3, CK1α, CDK4, MSK1/2 and casein kinase. Eryptosis-dependent shrinkage is induced by K+ efflux through Ca2+-activated K+ channel KCa3.1, the Gardos channel. Eryptotic cells are phagocytosed and may adhere to endothelial cells. Eryptosis may help prevent hemolysis since defective erythrocytes usually undergo eryptosis followed by rapid clearance from circulating blood. Excessive eryptosis stimulated by various diseases and xenobiotics may result in anemia and/or impaired microcirculation. This review focuses on the significance and mechanisms of eryptosis as well as on the ion fluxes involved. Moreover, a short summary of further ion transport mechanisms of the erythrocyte membrane is provided.